Predicting Self-Worth from Attachment Security and Social Feedback Sensitivity - Kalogeropoulos, Dimitra; Papadopoulos, Eleni; Antoniou, Nikos (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to investigate the predictive roles of attachment security and social feedback sensitivity in determining self-worth among university students.Methods and Materials: A correlational descriptive research design was used to examine the relationships between the variables. The sample consisted of 441 undergraduate students from various universities in Greece, selected based on the Krejcie and Morgan sample size determination table. Participants completed the Rosenberg Self-Esteem Scale (RSES) to assess self-worth, the Experiences in Close Relationships-Revised (ECR-R) to measure attachment security, and the Sensitivity to Social Feedback Scale (SSFS) to evaluate their responsiveness to social feedback. Data were analyzed using SPSS version 27. Pearson correlation coefficients were calculated to explore the bivariate associations between the variables, and multiple linear regression analysis was conducted to determine the predictive power of attachment security and social feedback sensitivity on self-worth.Findings: The results revealed a significant positive correlation between attachment security and self-worth (r = .61, p < .01) and a significant negative correlation between social feedback sensitivity and self-worth (r = –.47, p < .01). Multiple regression analysis indicated that the model significantly predicted self-worth, F(2, 438) = 186.72, p < .001, with R² = .46. Both attachment security (β = .54, p < .001) and social feedback sensitivity (β = –.29, p < .001) emerged as significant predictors, together accounting for 46% of the variance in self-worth.Conclusion: The findings highlight the crucial role of both early relational security and ongoing interpersonal feedback in shaping self-worth among young adults. Enhancing attachment security and reducing maladaptive sensitivity to social feedback may be effective pathways for promoting healthier self-concepts in emerging adulthood.